(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Progressive failure is a catastrophic phenomenon in structures that can happen due to natural disasters or human factors. In the progressive failure mechanism, a single local failure may cause substantial deformation that leads to the collapse of a structure. The numerous life and financial losses that may occur in the structure due to the progressive failure mechanism make it essential to study the strength and capacity of the structures against this phenomenon. In the current study, diverse scenarios of column removal are analyzed on the progressive failure process of a 10-story steel frame. The frame in question has a distinct bending frame system that is designed and controlled regarding internal regulations. The progressive failure process is done by the alternative load path method with different column removal scenarios in OpenSees software, nonlinear static analysis (push down), and based on GSA instructions using the load path method. The results of this study reveal that in all the studied cases, by changing the column removal position from the ground floor to the upper floors, it is observed that the resistance force of the frame against progressive failure is reduced. With each change in the column removal position, the resistive force decreases by an average of 10.24% compared to its previous state. In all cases of changes in column removal position from the corner column to the side and middle, it can be seen that the behavior of the frame due to removing the side and middle columns is quite similar and the maximum force of the frame against progressive failure increases by 98.5% averagely.